Truth and beauty : aesthetics and motivations in science - Chandrasekhar, Subrahmanyan (London; The University of Chicago Press, 1992)
This book is a motivation for scientists and mathematicians.
Keywords: Physics--Philosophy; Motivation (Psychology)